PENGALAMAN GURU DALAM MEMBANTU KELANCARAN KETERAMPILAN MEMBACA PADA SISWA KELAS 1 MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN - Khairatussyifa Amalia; Henri Peranginangin Tanjung; Iis Susiawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore teachers’ experiences in supporting the fluency of reading skills among first-grade students at Ma’had Al-Zaytun Islamic Elementary School. Reading is a fundamental skill that serves as the foundation for all learning activities at the primary level. Without adequate reading ability, students often face difficulties in understanding other subjects. This research employs a qualitative descriptive approach with a phenomenological design to describe the authentic experiences of teachers in reading instruction. Data were collected through classroom observations, in-depth interviews with the first-grade teacher as the main informant, and documentation of teaching activities and student outcomes. The findings show that the teacher applied the Structural Analytic Synthetic (SAS) method, which was effective in helping students recognize whole words, break them down into syllables and letters, and simultaneously understand the meaning of texts. The teacher also implemented scaffolding strategies by grouping students according to their reading abilities, providing intensive assistance to struggling readers, and encouraging fluent readers to practice independently. Various teaching media were used, such as Bacalah books, syllable cards, KV charts, phonics games, and interactive visual aids, which enhanced student engagement and motivation. The main challenges included differences in students’ reading proficiency, lack of concentration, and difficulties in distinguishing similar letters. Supporting factors consisted of adequate school facilities, curriculum support, and the teacher’s creativity in designing enjoyable learning activities. This study concludes that teachers’ experiences play a crucial role in developing effective strategies for early reading instruction and may serve as a useful reference for both teachers and educational institutions in improving literacy at the primary level. Keywords: teacher experience, reading skills, first-grade students, SAS method